Poetry on the tongue of the other, a media vision. The poetry of Abu Marwan al-Jaziri (396 AH) is an example - Khalaf Hussein, Sabreen ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The other represents a key element in the creative process. It is a stimulus for saying a text. It is considered as a branch for the meanings and notions. Also, it calls for justifications. It has been observed in the poetry of Abi Marwan Aljazeeri. Although we received little of his poetry, most of it had been said by the janitor of Almansour by a request for responding on the events’ requirements. Aljazeeri was not just his poet, but he was his companion. When the janitor of Almansour found out that the poet has had literary prowess in formulation and his consistent words accompanied with an urgent need to poetry as a means of media, he appointed the poet as media spokesman on behalf ofhis Alamriya State. He worked to talk about his virtues and beautify his vices. Moreover, he appointed him in administrative missions since the janitor of Almansour found out that Aljazeerihas political acumen besides his literary efficiency.